부동산 보유세의 역진성과 전세가 귀착효과 - 최충익; Choi Choongik; 김철민; Kim Chulmin; 이동관; Lee Dongkwan; 김천일; Kim Chunil (감정평가학 논집, 2020)
본 논문은 부동산 보유세의 역진성과 전세가 귀착효과를 파악하기 위해 실증분석하고 있다. 보유세 개편을 두고 다양한 논의들이 이루어졌지만 부동산 보유세가 주택보유자에게 경제적으로 얼마나 부담이 되는지에 대한 담론과 보유세가 상승할 경우 이를 세입자에게 전가시킬 것인지에 대한 실증적 논의는 제대로 이루어지지 못했다. 이에 본 논문에서는 주택 보유자의 사회경제적 특성 파악을 토대로 부동산 보유세의 역진성 및 전세가 귀착효과에 대한 실증분석을 하고 있다. 분석자료로 주택소유자 개별특성을 파악할 수 있는 마이크로 데이터를 사용하여 실제 주택보유자의 특징을 분석하고 서울시 전세 실거래가를 토대로 부동산 보유세의 전세가 귀착효과를 분석하였다. 분석결과 소득계층별 보유세 부담의 역진성은 뚜렷하게 나타났다. 재정패널자료를 통해 주택보유가구의 보유세 부담을 소득수준별에 따라 분석한 결과 가구소득 1분위부터 4분위까지 소득계층별 세부담의 역진성이 발견되었다. 또한 종합부동산세 대상 아파트가 종합부동세 납부 대상이 아닌 아파트에 비해 전세가격이 높지 않게 나타났으며, 종부세 부과에 따른 전세금 전가효과는 분석결과 나타나지 않았다. 이는 전가시킬 만큼의 충분한 종합부동산세가 부과되지 않았기 때문일 수 있으며, 종부세가 충분히 증가할 경우 전세금으로의 전가효과는 다른 결과를 나타낼 수 있음을 시사한다. This paper conducted empirical analyses in order to explore the incidence effect of real estate tax on the Jeonse costs and the regression of the property tax. Recently, various discussions have been made over the reformulation of property tax, but the discourse on how much the tax is economically burdened to homeowners and whether the increase in the tax will be passed onto tenants has not been properly investigated. The purpose of this study is two fold. First, we analyzed the real estate tax burden by income class using the Public Finance Panel Survey data. Finally, we explored the possibility of the incidence of real estate tax on the Jeonse tenants by employing a simple quasi-experimental design. We found the Jeonse prices for the apartments, which are subject to the comprehensive real estate tax, are not higher than those for the apartments, which are not subject to the comprehensive tax. This indicates that (1) there is no evidence on the incidence of the tax on the Jeonse tenants, and (2) the amount of tax levied is not enough to trigger the incidence. We expect that the pattern of the incidence would turn to the different direction if the tax rates rise.